Orf Virus Encoded Protein ORFV119 Induces Cell Apoptosis Through the Extrinsic and Intrinsic Pathways - Li, Wei; Chen, Huiqin; Deng, Hao; Kuang, Zhenzhan; Long, Mingjian; Chen, Daxiang; Liao, Xiaoqing; Li, Ming; Rock, Daniel L.; Luo, Shuhong; Hao, Wenbo (Frontiers in Microbiology, 2018)
Apoptosis, a significant form of cell death, has a leading role in the host cell defense against virus infection. Viruses have evolved a series of strategies that block apoptosis during the early stage of viral infection to enhance viral replication, and induce apoptosis in the late stages to facilitate viral particle release from the cells. Here we show that orf virus (ORFV), the causative agent of orf, encodes an apoptosis-inducing protein ORFV119. ORFV119 targets the mitochondria in host cells, inhibits cell proliferation, and induces cell apoptosis. Protein array data indicated that ORFV119 could induce apoptosis via up-regulation of Smac, Bak and Bax and down-regulation of anti-apoptotic proteins Bcl-2 and cIAP-2. Activation of caspase-9 and caspase-3, and consequent PARP cleavage, ultimately lead to apoptosis. ORFV119 could also directly activate caspase-8 and induce Bid, involved in the extrinsic pathway, to achieve cell death. Furthermore, sequence analysis and experiments with mutants of ORFV119 introducedrevealed that ORFV119 contains a key N-terminal domain that is necessary and sufficient to direct the protein to the mitochondria. Together, we report, for the first time, the identification of the novel apoptosis-inducing protein ORFV119 encoded by a parapoxvirus. This provides an important reference for the study of pathogenesis, identification of immunomodulation mechanisms of ORFV, and may lead to new strategies for orf disease control.